Utility bill reimbursement from BUCG-ABC JV for the period from January-2020 to December-2020 - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the invoices of utility bill reimbursement from BUCG-ABC JV for BRACU new campus project.